2013
DOI: 10.1002/jbm.b.33067
|View full text |Cite
|
Sign up to set email alerts
|

Intergranular pitting corrosion of CoCrMo biomedical implant alloy

Abstract: CoCrMo samples of varying microstructure and carbon content were electrochemically corroded in vitro and examined by scanning electron microscopy and electron backscatter diffraction techniques. The rate of corrosion was minimized (80% reduction from icorr = 1396 nA/cm(2) to icorr = 276 nA/cm(2) ) in high-carbon CoCrMo alloys which displayed a coarser grain structure and partially dissolved second phases, achieved by solution annealing at higher temperatures for longer periods of time. The mechanism of degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 43 publications
1
36
1
Order By: Relevance
“…It also has been reported that the current recorded at the transpassive zone was not dominated by chromium dissolution but by other electrochemical reactions as water oxidation, the presence of pits and the influence of the BSA (protein) in the growth of the passive and protective film [57,58]. Therefore, at potentials higher than ~ + 0.56 V, the localized corrosion on the CoCrMo substrate surface immersed in SBF+BSA, could have started in the grain boundaries or in some specific weak points of the passive layer [59]. A semi quantitative analysis by means of Energy-Dispersive X-ray spectroscopy (EDS) was made on the surface inside the pit (see Figure 8b ), the results obtained For the case of samples coated with the multilayer, the following can be observed.…”
Section: Corrosionmentioning
confidence: 99%
“…It also has been reported that the current recorded at the transpassive zone was not dominated by chromium dissolution but by other electrochemical reactions as water oxidation, the presence of pits and the influence of the BSA (protein) in the growth of the passive and protective film [57,58]. Therefore, at potentials higher than ~ + 0.56 V, the localized corrosion on the CoCrMo substrate surface immersed in SBF+BSA, could have started in the grain boundaries or in some specific weak points of the passive layer [59]. A semi quantitative analysis by means of Energy-Dispersive X-ray spectroscopy (EDS) was made on the surface inside the pit (see Figure 8b ), the results obtained For the case of samples coated with the multilayer, the following can be observed.…”
Section: Corrosionmentioning
confidence: 99%
“…20,22 Especially, the pitting corrosion reported by Gilbert et al revealed similar features such as egression of particles from surface and the intergranular corrosion as we observed in this study. 22 Recent laboratory tests suggested that pitting corrosion could happen at carbide boundaries and high energy grain boundaries in electrochemically corroded CoCrMo samples, [23][24][25] especially, in the presence of initial high contact pressure 26 and proteins. 27 The stress may tear the carbides off from the surface 26 and the presence of proteins may lower the pitting potential leading to localized chemical attack.…”
Section: Discussionmentioning
confidence: 99%
“…There are various reports of pitting in retrieved Co-Cr [44] implants and during simulated electrochemical testing [66], although it does not seem to be the dominant mode of corrosion in-vivo [67]. Potentiostatic polarization tests indicate that reducing carbon content in as-cast ASTM F75 increases pitting corrosion resistance, due increased chemical and homogenity [68].…”
Section: Pitting Corrosionmentioning
confidence: 98%